2015
DOI: 10.1074/jbc.m115.656140
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation of Glutathione S-Transferase P1 (GSTP1) by Epidermal Growth Factor Receptor (EGFR) Promotes Formation of the GSTP1-c-Jun N-terminal kinase (JNK) Complex and Suppresses JNK Downstream Signaling and Apoptosis in Brain Tumor Cells

Abstract: Background: GSTP1 is a downstream EGFR phosphorylation target. Results: EGFR-dependent C-terminal Tyr-198 phosphorylation shifts GSTP1 to the monomeric state, facilitates JNK binding and inhibition, and suppresses apoptosis in brain tumor cells. Conclusion: Enhanced suppression of JNK signaling by EGFR-phosphorylated GSTP1 provides a survival advantage for tumors. Significance: The GSTP1-EGFR cross-talk is a mechanism of tumor cell survival and drug resistance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
41
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(47 citation statements)
references
References 63 publications
6
41
0
Order By: Relevance
“…Among the mutants, one containing 12 alanine substitutions of the key receptor-binding residues was unable to bind β 2 -adrenoceptors but was able to inhibit JNK3 activation by wild type β-arrestin (Breitman et al, 2012). Similarly, it was recently reported that tyrosine phosphorylation of glutathione S-transferase P1, by the EGF receptor, favors the transferase interaction with JNK and inhibits downstream signaling of this MAP kinase pathway (Okamura et al, 2015). In addition, it has been observed that β 2 -adrenoceptors bind to membrane-associated guanylate kinase inverted-3 (MAGI-3) and that such association substantially retards ERK activation by the adrenoceptor (Yang et al, 2010).…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Among the mutants, one containing 12 alanine substitutions of the key receptor-binding residues was unable to bind β 2 -adrenoceptors but was able to inhibit JNK3 activation by wild type β-arrestin (Breitman et al, 2012). Similarly, it was recently reported that tyrosine phosphorylation of glutathione S-transferase P1, by the EGF receptor, favors the transferase interaction with JNK and inhibits downstream signaling of this MAP kinase pathway (Okamura et al, 2015). In addition, it has been observed that β 2 -adrenoceptors bind to membrane-associated guanylate kinase inverted-3 (MAGI-3) and that such association substantially retards ERK activation by the adrenoceptor (Yang et al, 2010).…”
Section: Discussionmentioning
confidence: 86%
“…However, there is evidence that mutants of signaling proteins and also of scaffolding proteins exert marked effects on the MAP kinase pathway, for example, β-arrestin 3 and glutathione S-transferase P1 (Breitman et al, 2012, Okamura et al, 2015). It is known that β-arrestins bind to GPCRs during their desensitization/signaling switch and that these proteins are involved in regulating the MAP kinase pathway (Breitman et al, 2012, Lefkowitz, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…[6][7][8][9] Moreover,i ti sk nown that GSTP 1-1 regulates the c-Jun N-terminal kinase (JNK) mitogenactivated protein kinase (MAPK)s ignaling pathway through a protein-protein interaction with the JNK and suppresses apoptotic signal transduction. [2,3,10] Thus, GSTP 1-1 is ag ood target for the development of inhibitors that might not only improvet he efficacy of anticancer drugs, butc ould also be used for anticancer therapy by itself. [3,4] Biochemical ands tructurala nalyses have shown that the GST family of proteins, including GSTP 1-1 ,f orm dimers.…”
mentioning
confidence: 99%
“…Also, glioblastoma cells involve dual Epidermal/GSTP1 in inducing functional inhibition of JNK signaling, with significant suppression of both spontaneous and drug-induced apoptosis in tumor cells [24]. The stabilization or destabilization of p53 illustrates potent mechanisms that are further propagated in terms of the enhanced pro-apoptotic actions of p53 versus an inherent tendency for increased destabilization as induced by Akt.…”
Section: Early-stage Cell Stressmentioning
confidence: 99%